INTEGRASI KARAKTER HAMBA TUHAN KEDALAM PELAYANAN DALAM BINGKAI TEOLOGI MATHEUS MANGENTANG - Malik Bambangan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
The determinant of success in one's service is sustained by good and true character. Various attempts were made by educational institutions to implement character building in the learning process. But how can success in service if they do not have good character like Christ's character? The purpose of this study is to reduce the teaching of the theology of Matheus Mangentang about the character of God's servants in ministry at Sekolah Tinggi Teologi Injili Arastamar (hereinafter abbreviated SETIA) Jakarta and Gereja Kristen Setia Indonesia (hereinafter abbreviated as GKSI). The method used is an interview with Matheus Mangentang as the primary source of data and collecting data on centralization relating to the discussion of this topic. As a result, the character of God's servants in the theology of Matheus Mangentang is still relevant and can be integrated in the service of God's servants in SETIA and GKSI. The conclusion of this study is that the character of God's servants in the framework of the theology of Matheus Mangentang is very much needed in carrying out special services in SETIA and GKSI.